Rynek zamówień publicznych - determinant informacji dla rachunkowości zarządczej na przykładzie samodzielnych zakładów opieki zdrowotnej - Lewandowska, Hanna (Public Order Market as a Determinant of Management Accounting, 2007)
Outsourcing represents a new strategy of managing the entity (eg. independent health care institutions) which aims at lowering costs of economic activity (in case of the orderers). Selecting cost centres and time-value analysis (cost analysis) allow for specifying the abbreviation from the real cost. Information carriers included in the analyzed quantities referring to the demand and supply of public procurement market may also be used to determine in ex ante terms the area of business activity risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 362-370